Good corporate governance, economic growth and sustainable development in Namibia's public sector - Zinatsa- Muswaka, P.; Chilunjika, Alouis (Journal of Public Administration and Development Alternatives, 2022)
Good corporate governance is understood as the critical element that facilitates the achievement of development through strengthening and stepping up the velocity of economic performance and progression in the public sector. This makes it imperative for the integration of good governance into corporate governance in order to achieve sustainable development in Namibia. This paper reveals how the good corporate governance framework can encroach upon and fortify the development of micro-economic efficiency and effective capital markets within the Namibian public sector. It seeks to provide an economic rationale for the importance of good corporate governance and explores the relationship between corporate governance performance and economic growth. The paper also aims to reveal the various models of corporate governance and their contribution in bringing about liberalised capital markets and significant escalation in capital inflows. The paper’s thrust is on establishing good corporate governance as a crucial benchmark for instituting a salient investment that is essential in augmenting sound leadership, sustainability, as well as economic growth and development in Namibia.